Evaluation of laser induced breakdown spectroscopy in view of nickel and vanadium on-line determination in petroleum products. Issue 3 (12th January 2016) - Trichard, F.; Gilon, N.; Lienemann, C. P.; Baco-Antoniali, F.
Abstract : Laser induced breakdown spectroscopy (LIBS) has been evaluated for the purpose of analyzing petroleum products. Optimization in view of on-line LIBS control is presented. Abstract : On-line nickel and vanadium determination in oil samples was proposed using laser induced breakdown spectroscopy to reach low mg kg −1 concentrations. Both 266 nm and 532 nm emissions of a neodymium YAG laser were evaluated and the visible wavelength gave better results. An original optimization strategy employing a Doelhert design and full quadratic model was carried out. The number of laser shots, the delay time, the integration time gate and the laser energy were selected as factors. Measurements were compared under static and dynamic conditions ( i.e. the sample being moved at a cc h −1 flow rate as it is under the process conditions), and no significant difference in terms of sensitivity and detection limits was observed due to the viscous nature of oil samples. Detection limits achieved for vanadium were 7 mg kg −1 and 31 mg kg −1 for nickel. In view of on-line measurements a Czerny Turner spectrometer equipped with a photomultiplier was evaluated. Then, the LIBS method developed enabled the plot of linear calibration curves for Ni and V with a sensitivity in agreement with the need of the petroleum industry for on-line determination.